Expert testimony by linguists in U.S. courts: An illustrative case of practices - Finegan, Edward (Language and Law / Linguagem e Direito, 2021)
This article describes procedures surrounding expert testimony in U.S. federal courts, exemplifying with details of an expert’s experience in one case. The exemplar is a civil (not criminal) case brought for defamation, tried to a jury in a federal district court, and subsequently appealed to a higher court. The article discusses reasons for which attorneys retain expert linguists, why courts welcome experts when their testimony is deemed helpful in deciding a disputed fact but exclude them if they are not qualified or the profered testimony is deemed insuficiently helpful or possibly prejudicial to a jury. The article concludes with observations about the pros and cons of serving as a linguistics expert in contested legal matters in an adversarial system.